The Pharmacological Activities of Crocus sativus L.: A Review Based on the Mechanisms and Therapeutic Opportunities of its Phytoconstituents. (14th February 2022) - Butnariu, Monica; Quispe, Cristina; Herrera-Bravo, Jesús; Sharifi-Rad, Javad; Singh, Laxman; Aborehab, Nora M.; Bouyahya, Abdelhakim; Venditti, Alessandro; Sen, Surjit; Acharya, Krishnendu; Bashiry, Moein; Ezzat, Shahira M.; et al.
Abstract : Crocus species are mainly distributed in North Africa, Southern and Central Europe, and Western Asia, used in gardens and parks as ornamental plants, while Crocus sativus L. (saffron) is the only species that is cultivated for edible purpose. The use of saffron is very ancient; besides the use as a spice, saffron has long been known also for its medical and coloring qualities. Due to its distinctive flavor and color, it is used as a spice, which imparts food preservative activity owing to its antimicrobial and antioxidant activity. This updated review discusses the biological properties of Crocus sativus L. and its phytoconstituents, their pharmacological activities, signaling pathways, and molecular targets, therefore highlighting it as a potential herbal medicine. Clinical studies regarding its pharmacologic potential in clinical therapeutics and toxicity studies were also reviewed. For this updated review, a search was performed in the PubMed, Science, and Google Scholar databases using keywords related to Crocus sativus L. and the biological properties of its phytoconstituents. From this search, only the relevant works were selected. The phytochemistry of the most important bioactive compounds in Crocus sativus L. such as crocin, crocetin, picrocrocin, and safranal and also dozens of other compounds was studied and identified by various physicochemical methods. Isolated compounds and various extracts have proven their pharmacological efficacy at the molecular level and signaling pathways both in vitro and in vivo . In addition, toxicity studies and clinical trials were analyzed. The research results highlighted the various pharmacological potentials such as antimicrobial, antioxidant, cytotoxic, cardioprotective, neuroprotective, antidepressant, hypolipidemic, and antihyperglycemic properties and protector of retinal lesions. Due to its antioxidant and antimicrobial properties, saffron has proven effective as a natural food preservative. Starting from the traditional uses for the treatment of several diseases, the bioactive compounds of Crocus sativus L. have proven their effectiveness in modern pharmacological research. However, pharmacological studies are needed in the future to identify new mechanisms of action, pharmacokinetic studies, new pharmaceutical formulations for target transport, and possible interaction with allopathic drugs.